A 2014 Medical Informatics Perspective on Clinical Decision Support Systems: Do We Hit The Ceiling of Effectiveness? - Bouaud, J.; Lamy, J.-B.; Section Editors for the IMIA Yearbook Section on Decision Support (Yearbook of Medical Informatics, 2014)
Objective: To summarize recent research and propose a selection of best papers published in 2013 in the field of computer-based decision support in health care.Method: Two literature reviews were performed by the two section editors from bibliographic databases with a focus on clinical decision support systems (CDSSs) and computer provider order entry in order to select a list of candidate best papers to be peer-reviewed by external reviewers.Results: The full review process highlighted three papers, illustrating current trends in the domain of clinical decision support. The first trend is the development of theoretical approaches for CDSSs, and is exemplified by a paper proposing the integration of family histories and pedigrees in a CDSS. The second trend is illustrated by well-designed CDSSs, showing good theoretical performances and acceptance, while failing to show a clinical impact. An example is given with a paper reporting on scorecards aiming to reduce adverse drug events. The third trend is represented by research works that try to understand the limits of CDSS use, for instance by analyzing interactions between general practitioners, patients, and a CDSS.Conclusions: CDSSs can achieve good theoretical results in terms of sensibility and specificity, as well as a good acceptance, but evaluations often fail to demonstrate a clinical impact. Future research is needed to better understand the causes of this observation and imagine new effective solutions for CDSS implementation.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; decision support systems